(3eONd JWHjbj eYGUQs - (3GMeO Mdej(B, (3LeYIs; (3GdYQHjO(B, (3YUGe agOs ((3YeGf(B:s (3OGQ GdefGgL(B,s, 2007)
(3JfGhd GdcJGH fXe GdeYdheGJ GdeMGSHjI ef NdGd JYQVg dYTQI ehVhYGJ QFjSjI TZd cd efgG CMO CLRGA GdcJGH aJfGhd GdaUd GdChd GdeMGSHI cfXGe ddeYdheGJ, hGdaUd GdKGfj GdhXGFa GdCSGSjI dfXGe GdeMGSHI GdEdcJQhfjI hGdaUd GdKGdK GdhXGFa GdCSGSjI dfXGe JTZjd GdHjGfGJ GdeMGSHjI hGdaUd GdQGHY EONGd GdHjGfGJ GdeMGSHjI EdcJQhfjkG, hGdaUd GdNGeS JfXje GdHjGfGJ GdeMGSHjI EdcJQhfjkG, hGdaUd GdSGOS eYGdLI GdHjGfGJ GdeMGSHjI EdcJQhfjkG, hGdaUd GdSGHY(B: (3GSJNOGe GdHQGeL GdLGgRI aj JWHjbGJ GdeMGSHI GdeGdjI hGdaUd GdKGef(B: (3JWhQ feGPL bjGS bjeI GdeYdheGJ GdeMGSHjI, GdaUd GdJGSY(B: (3GdeYdheGJ GdeMGSHjI hGJNGP GdbQGQ, hGdaUd GdYGTQ(B: (3JcfhdhLjG Cef GdeYdheGJ GdeMGSHjI(B. s
(3HjHdjhZQGajG U(B.361s
Keywords: (3eMGSHIs; (3eYGdLI GdHjGfGJ s; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s